2017
DOI: 10.1155/2017/3138254
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes and Their Polymorphism Influences the Risk of Knee Osteoarthritis

Abstract: Introduction Genetic factors including the level of expression of the fingerprint of genes involved in the development of bones and cartilage such as GDF-5 or ESR-α or CALM-1 are known to be strong determinants of the osteoarthritis (OA) in Caucasian and Oriental populations. Because of high prevalence of OA in Indian population and availability of limited genetic data, we determined whether similar genetic factors are involved in Indians as well. Methods A case control study was carried out involving 500 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Five case-control studies involving a total of 2183 OA patients 2654 healthy control subjects were identified and included in our meta-analysis. The studies were performed in the UK, [ 34 ] India, [ 33 ] Greece, [ 32 ] China, [ 31 ] and Japan, [ 35 ] respectively, the sample-size ranged from 351 to 1672. Three of 5 included studies [ 31 33 ] focused on the association between rs12885713 and KOA while the remaining 2 studies [ 34 , 35 ] featured to assess the association in HOA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five case-control studies involving a total of 2183 OA patients 2654 healthy control subjects were identified and included in our meta-analysis. The studies were performed in the UK, [ 34 ] India, [ 33 ] Greece, [ 32 ] China, [ 31 ] and Japan, [ 35 ] respectively, the sample-size ranged from 351 to 1672. Three of 5 included studies [ 31 33 ] focused on the association between rs12885713 and KOA while the remaining 2 studies [ 34 , 35 ] featured to assess the association in HOA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they also demonstrated the CALM1 expression level in human OA cartilage tissue was significantly higher than that in cultured normal human articular chondrocytes. [ 35 ] Mishra et al [ 33 ] reported that the reduced mRNA and protein expression level of CALM1 in the peripheral blood lymphocytes from OA patients appeared to be parallel to the decreased formation of cartilage as well as its disruption. These findings altogether suggested that CALM1 participated and played an important role in the OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Five of included citations [ 17–21 ] studied the association between the rs12885713 polymorphism of the CALM1 gene and risk of OA. Mishra et al [ 19 ] and Mototani et al [ 17 ] found that the TT genotype of the rs12885713 polymorphism increases the risk for OA, while Shi et al [ 21 ], Poulou et al [ 20 ], and Loughlim et al [ 18 ] did not find a significant correlation between the rs12885713 polymorphism and OA risk. More characteristics of the included citations are shown in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The rs3814843, rs2300500, and rs3179089 polymorphisms of the CALM1 gene were investigated in only one study [ 17 , 19 ], which reported significant associations ( Table 2 ). Nevertheless, further replication studies are required to confirm the associations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation